Implementation of decentralised food procurement programmes and the impact of the policy, institutional and legal enabling environment: The case of PRONAE and PAA Africa in Mozambique - Luana F. Joppert Swensson; Israel Klug (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
The development and implementation of an efficient institutional food procurement programme (IFPP) - which aims to link smallholder producers to institutional markets and promote development of food supply systems - is not a simple or straightforward task. It requires a series of conditions that must be coordinated and matched together. These conditions depend on - but go far beyond - governmental will and the availability of demand. […]
Keywords: 330; Implementation; decentralised; food; procurement; programmes; impact; policy; institutional; legal; enabling; environment; case; PRONAE; PAA Africa; Mozambique